Natural Landscape Planning as Tsunami Disaster Mitigation: A Case in Uleu Lheue, Banda Aceh, Indonesia - Meutia, Zya Dyena (TDMRC, Universitas Syiah Kuala, 2022)
Tsunami has changed the landscape of the area, the environmental order (spatial planning), and the structure of the Ulee Lheue Coastal area. The tsunami threat is substantial since the site's position is very close to the source of the disaster. The shape of the area is flat and does not have any protection (both natural and structural) to protect the land. Planning criteria in tsunami areas are essential to know and learn from previous disasters. Tsunami disasters have different characteristics in each site; thus, planning is mismanaged and ineffectively conducted. Planning is performed by applying the tsunami mitigation approach and the theory of landscape connectivity. One of the mitigation plans is planning a natural landscape in the form of vegetation. The vegetation in the research case study is in the coastal area of Uleu Lheue, which was still lacking after the tsunami hit this area in 2004. There are only mangroves in some areas, sea pine, tamarind trees, and low shrubs. Therefore, in planning a mitigation-based site, it is necessary to arrange vegetation to reduce the impact of a tsunami and condition the environment around the area. This research aims to integrate natural landscape planning based on tsunami mitigation and find natural vegetation or natural protection as a tsunami disaster mitigation and as a criterion in planning a coastal area based on tsunami disaster mitigation. From the results of the tsunami study, it is recommended that the case study area be freed from new development and mitigation strategies with buffers in the form of using vegetation zones (mangroves and the like). The planning applied using vegetation indicated to reduce the effects of the tsunami that hit the design area, among others, the tree category: Pandanus Odoratissimus, Casuarina equisetifolia, Hibiscus Tiliaceus, Tamarindus indica, Anacardium occidentale, bakau, nypah and waru.